Contemporary Approaches To Translating English Publicistic Texts - Tukhlieva Gavkhar (Academia One Publishing, 2025)
To analyze methods for translating precedent texts, it is useful to pay attention to the approaches of Y. Naida and A. Neubert. Neubert emphasizes the importance of pragmatic adequacy of translation, which requires preserving the communicative effect of the original. This means that the reader's reaction to the translation should be similar to the reaction to the original. Based on this, Neubert believes that only minimal changes to the translation need to be made. At the same time, Naida suggests using a variety of notes, footnotes, and cultural commentary to maintain an understanding of the cultural differences between the original and the translation
Keywords: linguoculture; translation; recipient; music culture